Fraser reads "Never Let Me Go". A lesson on justice in three dimensions - Cavaliere, Anna (Scenari, 2023)
In her essay On Justice, Nancy Fraser analyses the three dimensions of her conception of justice (redistribution, recognition and representation) starting from a literary text: Kazuo Ishiguro’s novel, “Never let me go”. Fraser’s thesis, which we critically analyse in this contribution, is that Ishiguro’s book, which seems to be just a dystopian novel and the tale of an adolescent love story, actually contains valuable insights into the theme of justice and allows us to reflect on the most insidious forms of injustice that characterise contemporary society.